Nitrogen deposition to forest ecosystems with focus on its different forms - Hůnová, I; Kurfürst, P; Stráník, V; Modlík, M (The Science of the total environment, 2017)
UNLABELLED: Time trends and spatial patterns for wet nitrogen deposition in view of its reduced and oxidized forms for Czech forests are presented. Time trends in NH4+, NO3-, and N-NH4+/N-NO3- ratio at 15 sites in 1990-2014 were analysed using the Mann-Kendal test. Changes in spatial patterns derived from results of 43 sites in 2005-2014 were also assessed. Our results indicated a slow but convincing change in favour of NH4+. The N-NH4+/N-NO3- ratio, both in precipitation and wet deposition, has been increasing steadily, reflecting the changes in reduced and oxidized forms of nitrogen emissions. A similar change has been observed in some other regions and might have negative impacts on ecosystems. CAPSULE: N-NH4+/N-NO3- ratio in precipitation and deposition changes in favour of NH4+. This reflects changes in emissions and might have implications for ecosystems.
Keywords: Reduced nitrogen; Oxidized nitrogen; Emissions; Atmospheric deposition; Forests